Review on adaptation of augmented reality as training and learning methods in manufacturing and industrial engineering. (14th December 2021) - Alahakoon, Yoshika; Kulatunga, Asela K.
Augmented reality (AR) is dispersed in the manufacturing and industrial engineering disciplines due to its ability of actualising situations, which could not be replicated using physical means. Besides the fact that many reviews have been carried out in the areas of AR training, learning methods and tools of distant learning, this paper identifies the areas which are not previously fully grasped by the previous literature. This study is followed by an extensive bibliometric and content analysis with the bibliometric analysis focused on the country-wise, document-wise, keyword-wise and year-wise contributions. Through content analysis, the state of the art AR technologies, current methods of AR learning and training concepts and pervasion of AR tools and their drawbacks were identified. The findings of this systematic review reveal that more real applications and virtual environments should be facilitated instead of conceptual approaches for distant learning as well as for the manufacturing and industrial context.